2013
DOI: 10.4274/vhd.66375
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiyaliz Hastalarında HBV, HCV ve HIV Seroprevalansı ve Hepatit B Aşılaması ile Oluşan Antikor Cevabının Değerlendirilmesi

Abstract: Ge liş ta ri hi/Re cei ved: 15.08.2013 Ka bul ta ri hi/Ac cep ted: 09.10.2013 © Viral Hepatit Dergisi, Ga le nos Ya y› ne vi ta ra f›n dan ba s›l m›fl t›r. / Viral Hepatitis Journal, pub lis hed by Ga le nos Pub lis hing. ABS TRACT Objective: In this study; we aimed to determine the the effectiveness of infection control measures in patients undergoing hemodialysis for chronic renal failure by analyzing the HBsAg, anti-HBs, anti-HCV and anti-HIV serologic indicators retrospectively. Materils and Methods: HBsAg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Studies conducted in our country have shown that hemodialysis patients have anti-HCV positivity at rates ranging from 1.2% to 16% (2,4,(14)(15)(16)(17)(18)(19). Among international studies, the prevalence of anti-HCV was determined as 4.3% by The rate of anti-HIV positivity in our dialysis centeris higher than those reported in other Turkish studies.…”
Section: Discussionmentioning
confidence: 52%
“…Studies conducted in our country have shown that hemodialysis patients have anti-HCV positivity at rates ranging from 1.2% to 16% (2,4,(14)(15)(16)(17)(18)(19). Among international studies, the prevalence of anti-HCV was determined as 4.3% by The rate of anti-HIV positivity in our dialysis centeris higher than those reported in other Turkish studies.…”
Section: Discussionmentioning
confidence: 52%
“…Accordingly, while mild stimuli create satisfaction and pleasure, stronger stimuli create a penalty effect. Thus, using a very intensive stimulation for rewarding, we cause to unfavorable effect so, desired behavior becomes a behavior to be avoided (5).…”
Section: Evaluation Of Methods Used and Conclusion With Regard To Ethical-social-legal Aspectsmentioning
confidence: 99%
“…Since the etiology of violence depends on one's experience and his/her genes, the treatment methods should start with changing these experiences and changing the genetic activity by epigenetic acquisition. If environmental impulses could change one's brain by means of neural plasticity forcing to learn the good skills, and forcing to be a good person, we could have decreased the violence in the next generations (5). May be the violence in that community could be erased and from the brains.…”
Section: Memory Neurochemistry and 'Immediate Early Genes'mentioning
confidence: 99%
See 1 more Smart Citation